In vitro assessment of human enamel surface composition bleached with two different bleaching agents - Nazish Fatima Ahmed (Wolters Kluwer Medknow Publications, 2019)
Background: Varieties of methods are available for more obstinate tooth discoloration such as crowns, veneer, and micro and macro abrasion of enamel, but tooth bleaching gained high patient acceptance. The aim of the present research was to estimate changes in surface enamel composition after bleaching 16% carbamide peroxide (CP) (home-use bleaching) with 38% hydrogen peroxide (HP) (in office bleaching). Materials and Methods: A total of 90 enamel slabs from 45 sound human third molars were randomly divided into three groups. Of three groups, per group had thirty samples (n = 30), of which samples of Group 1 were placed in artificial saliva at 37°C in incubator (Memart, Germany) during complete experiment. Sample of Groups 2 and 3 was treated with power whitening gel (White Smile 2011, Germany) and tooth whitening pen (white Smile 2011, Germany), respectively. Later on, after bleaching treatment, discs were thoroughly washed and stored in artificial saliva at 37°C in incubator. Chemical analysis was done with energy dispersive spectroscopy (Edx) detector to detect changes in surface composition. Results: Energy dispersive X-ray spectroscopy (Edx) analysis showed no significant difference between all the three groups for Ca% mass (P > 0.99) and Ca% atomic (P > 0.99), C% mass (P = 0.78) and C% atomic (P = 0.76), and O% mass (P > 0.99) and O% atomic (P = 0.28). Similar results were shown for Na, Mg, P, and F. Conclusion: Statistically insignificant effect was observed on enamel composition with both bleaching agents (38% HP and 16% CP).